Analysis of the Influence of Direct Investment and Labor on Economic Growth in Indonesia - Epriyanti, Meri; Sunoto, Sunoto (Indonesian Journal of Banking and Financial Technology, 2024)
This study aims to analyze the effect of investment and labor on economic growth in Indonesia. One of the factors that affects economic growth is foreign direct investment (FDI). In addition to FDI, labor also plays an important role in economic growth. This study uses secondary data in the form of a thirteen-year time series from 2010-2023, namely with direct investment variables (X1) and Labor (X2). The analysis method used is quantitative, using Multiple Linear Analysis Techniques with the help of the E-Views 9 program. The results of this study indicate that direct investment and labor variables have a significant positive impact on economic growth in Indonesia.